Analyzing Civil Servant Competencies in The Implementation of The E-Performance Application: A Case Study of The Donggala Regency Village Community Empowerment Office - Muhammad Defri Syahputra; Rizki Amalia (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2025)
This research examines the competency of Civil Servants (PNS) in implementing the e-Performance application within the context of preparing and assessing Employee Performance Targets (SKP) at the Donggala Regency Village Community Empowerment Office. The e-Performance application is intended to streamline the management and monitoring of employee performance, thereby enhancing the effectiveness and efficiency of performance evaluation processes. Using a descriptive qualitative method, this research analyzes PNS competencies across five dimensions: Motives, Traits, Self-Concept, Knowledge, and Skills. The findings reveal that civil servants demonstrate adequate competency in the areas of Traits, Self-Concept, and Knowledge, while deficiencies remain in Motives and Skills. The main obstacles identified include low employee motivation, limited understanding of the e-Performance application, and insufficient outreach and technical training. To address these challenges, the research suggests increasing employee motivation, providing internal mentoring, and allocating budgets for outreach and technical training programs.